Swertia jayantii (Gentianaceae): a new species from North-East India - Srivastava, Amber; Khuraijam, Jibankumar Singh (Phytotaxa, 2024)
Swertia jayantii (Gentianaceae), a new species from Jaintia hills, Meghalaya, India is described here with photographic illustration. The new species is described under Swertia subgenus Ophelia sect. Ophelia due to the presence of single, naked nectary on each corolla lobe. It closely resembles S. cordata in having corolla lobes with blue-purple veins and quadrangular, narrowly winged stem. However, it can be distinguished by its deltoid-shaped nectary, calyx lobes shorter than corolla lobes, and obtuse leaf base. A taxonomic description showing detailed morphological characters with a key to the closely related species is provided here to facilitate its proper identification.